Shame/Honor, Guilt/Innocence, Fear/Power: A Missiological Response to Simon Cozens and Geoff Beech. (October 2018) - Whiteman, Darrell
There has been a significant increased interest among academic missiologists and mission practitioners in applying the concepts of shame/honor, guilt/innocence, and to a lesser extent fear/power, in cross-cultural ministry. This article responds to Simon Cozens's and Geoff Beech's contributions and notes the weaknesses of characterizing entire cultures as oriented to shame, guilt, or fear. Despite the caution of overgeneralization and stereotyping, there are some strengths in these concepts, which have been helpful in cross-cultural ministry. They should also be used to enable Western missionaries to discover the weaknesses and blind spots in their own ministry, biblical interpretations, and theology.